PERSEPSI YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN (Survey pada Aparatur Pemerintahan Kabupaten Aceh Utara) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2018)
This study aims to determine the effect of organizational commitment, the application of government accounting standards, and regional financial accounting information system to the quality of financial statements at the government apparatus of North Aceh Regency. Data was used in this study is primary of data by dividing questionnaires to 151 apparatus of government as a sample of this research. Data processing is done throgh multiple linear equations model. The results showed that: In partial organizational commitment has no significant effect to the quality of financial statements, the application of government accounting standards significantly influence to the quality of financial statements and utilization of financial accounting information system has significant effect to the quality of financial statements at the government apparatus of North Aceh Regency. Simultaneously organizational commitment, the application of government accounting standards and utilization of regional financial accounting information system have a significant effect to the quality of financial statements at government apparatus of North Aceh Regency. Organizational commitment, the application of government accounting standards and the utilization of regional financial accounting information systems have a strong relationship with the quality of financial statements in the government apparatus of North Aceh Regency. Organizational commitment, the application of government accounting standards and the utilization of regional financial accounting information systems have the ability to explain the effect on the quality of financial statements at the government apparatus of North Aceh Regency.